STUDENTS’ PERCEPTIONS TOWARDS USING GOOGLE SLIDES AND GOOGLE CLASSROOM AS ONLINE COLLABORATIVE TOOLS IN MANDARIN LEARNING - Chong Oi Leng; Chan Yann Sheng; Dr. Chun Keat Yeap; Choo Peng Tan (Journal of Islamic, Social, Economics and Development, 2021)
Covid-19 outbreak in Malaysia had a major impact on education. Lecturers have to shift from conventional face-to-face teaching to Open and Distance Learning (ODL) to continue delivering knowledge to their students. It was a big challenge for lecturers in the teaching of Mandarin as a foreign language which include listening, speaking, reading and writing skills. This situation would inevitably affect the learning outcome of the subject. Therefore, lecturers are exposed to technological learning tools and applied flipped classroom approach in teaching which prior use Google Applications namely Google Slides (a web-based presentation program, allowing comment and edit in real-time among teammates and lecturer) and Google Classroom (a web service which enables lecturer to create, share, comment and evaluate assignments in a collaborative teaching and learning environment) in Mandarin course. The use of technology in teaching is not only to enhance students’ learning but also to equip students with the technological and collaborative tools while preparing them for future academic. Surveys were conducted to a government university’s undergraduates taking Introductory Mandarin Level 1 in government undergraduate to elicit student perceptions of using the said applications to do language learning task and the effectiveness in building a collaborative learning environment. The results showed that this approach managed to boost up students’ participation in online learning, majority of the students prefer using such applications for future courses given that they can benefit from the lecturer’s immediate written feedback and easy access of course materials.